Clarification of public health pathways toward clinical careers: a pilot study describing a benchmark analysis project - Brown, Elizabeth A.; Feliciano, Melissa; Martinez, Daniel (Frontiers in Public Health, 2025)
IntroductionUndergraduate public health programs have adapted the required basic sciences based on medical and technological advances and the needs of the public health workforce. We aim to demonstrate how a benchmark analysis project was used to improve curriculum and develop a model where basic sciences in public health can be used to build pathways to clinical graduate programs like medicine, pharmacy, physician assistant, and dental.MethodsAuthors conducted a benchmark analysis of Bachelor of Science in Public Health (BSPH) Degrees (or public health-related degrees) in the southern region of the United States (US) to explore required basic sciences. Authors searched the Council on Education for Public Health’s website to identify accredited, baccalaureate public-health related degrees. The US Census Bureau’s Geographic Levels was used to define the southern region of the US. Inclusion criteria for public health-related programs included the following characteristics: (1) accredited as of October 2023, (2) located in the southern region of the US, and (3) Bachelor of Science. Authors used the American Medical College Application Service Application Course Classification Guide to categorize basic sciences into three categories: Biology, Chemistry, and Physics. Data were extracted to an Excel document for further review and analysis.ResultsThere were 38 accredited, baccalaureate public health-related programs in the southern region of the US that met the inclusion criteria. Eighteen programs (47.4%) had at least one concentration or track. Most programs required General or Introductory Biology (n = 12), Anatomy & Physiology (n = 9), General or Introductory Chemistry, or Microbiology (n = 5). Physics was counted twice as a required course while Cellular Biology (or Molecular Biology) and Organic Chemistry were counted once each across 38 programs.DiscussionThere are substantial differences across required basic sciences for BSPH Degrees in the southern region of the US. We offer a model of required basic sciences for BSPH leadership and students to consider adopting as they market BSPH Degrees for students interested in clinical careers and for those students not interested in clinical professions. This project and proposed model demonstrate that a BSPH Degree is a viable route to clinical careers, depending on a student’s academic and professional interests.